Impaired JAK-STAT signal transduction contributes to growth hormone resistance in chronic uremia - Schaefer, Franz; Chen, Yu; Tsao, Tanny; Nouri, Pouneh; Rabkin, Ralph (The journal of clinical investigation, 2001)
Chronic renal failure (CRF) is associated with resistance to the growth-promoting and anabolic actions of growth hormone (GH). In rats with CRF induced by partial renal ablation, 7 days of GH treatment had a diminished effect on weight gain and hepatic IGF-1 and IGFBP-1 mRNA levels, compared with sham-operated pair-fed controls.
Gesehen am 13.01.2021